Projekt „Owca” – refleksje pedagoga. O współpracy w działaniu - Prysak, Dorota (Studia Etnologiczne i Antropologiczne, 2017)
The Project “Sheep” resulted from the special educator and ethnologist cooperation, as addressing the need for using an experience and place by representatives of different scientific areas, the purpose of which was to combine professional competence in innovative teaching. The main goal was to raise funds to buy a sheep, then entrust it to the experienced shepherd from Koniaków who wanders along the Carpathians and reconstruct the old way of grazing. At the same time, the participation in this project has been used as an excellent opportunity to talk about building the local identity and cultural heritage values of the region and disabled people. This project also concerned people who are often barely visible in the human herd—people with disabilities.